Clinical effects of statins: focusing on simvastatin - D. M. Aronov; M. G. Bubnova (Кардиоваскулярная терапия и профилактика, 2009)
The role of statins in the treatment and secondary prevention of cardiovascular events and adverse outcomes among high-risk coronary heart disease patients is discussed, using well-known clinical trials on simvastatin as an example. Lipid-lowering and pleiotropic statin effects are analysed in detail, by age, gender, and clinical group.